A New Sound Sensitivity in the Current Tango. The Case of the Orquesta Típica Fernández Fierro. (Revista Argentina de Musicología, 2018)
The aim of this work is to study the sonorous and stylistic project of the Orquesta Típica Fernández Fierro, which crystallizes a change in the sound sensitivity of the genre today. The idea here is to analyze in what sense and under what conditions of production and reception makes possible the specificity of the sound constructed by the group, taking as an axis some aspects of the artistic and sonorous production of his last disc in study: Tics, tan idiotas como siempre (2013). In this case the principles of amplification, volume and distortion make the style of the group favoring a change in the way of sounding and of being listened.
Keywords: tango; sound sensitivity; listening; artistic production; sound recording